El pensamiento crítico a través de la comprensión lectora - Mosquera Garrochamba, Viviana Abigail (2025)
This research project aimed to identify strategies for developing critical thinking through reading comprehension. The goal was to help students not only develop the ability to comprehend what they read, but also to analyze, question, relate it to their daily lives, and argue their position. This is given that in the classroom, the strategies used are often mechanical and repetitive, greatly limiting the development of critical thinking in students. The study employed a qualitative, non-experimental design approach, utilizing non-participant observation and group interviews for data collection. Instruments included anecdotal records and open-ended questioning. Furthermore, the population selected through purposive, non-probability sampling consisted of 24 sixth-grade students from “Fe y Alegría” Elementary School. The selected strategies included reading hypotheses, deciphering textual clues, and news analysis, promoting active, reflective, argumentative, and collaborative reading. According to the results, it was evident that students significantly improved their ability to infer information, relate the text's information to their own reality, understand the author's ideas, express themselves effectively, and articulate their critical perspectives. They also demonstrated greater performance and interest in reading discussions, class participation, and the development of cognitive skills, such as synthesis, critical thinking, and decision-making skills. Therefore, it is concluded that the incorporation of these strategies in sixth-grade students not only strengthened skills such as reflection and argumentation but also promoted active, conscious, and collaborative reading, thus enriching their reading comprehension and critical judgment.